Combining Multiple Depth Cameras and Projectors for Interactions On, Above, and Between Surfaces - Wilson, Andy; Benko, Hrvoje (UIST '10 Proceedings of the 23nd annual ACM symposium on User interface software and technology, 2010)
Instrumented with multiple depth cameras and projectors, LightSpace is a small room installation designed to explore a variety of interactions and computational strategies relat-ed to interactive displays and the space that they inhabit. LightSpace cameras and projectors are calibrated to 3D real world coordinates, allowing for projection of graphics correctly onto any surface visible by both camera and projector. Selective projection of the depth camera data enables emulation of interactive displays on un-instrumented surfaces (such as a standard table or office desk), as well as facilitates mid-air interactions between and around these displays. For example, after performing multi-touch interactions on a virtual object on the tabletop, the user may transfer the object to another display by simultaneously touching the object and the destination display. Or the user may “pick up” the object by sweeping it into their hand, see it sitting in their hand as they walk over to an interactive wall display, and “drop” the object onto the wall by touching it with their other hand. We detail the interactions and algorithms unique to LightSpace, discuss some initial observations of use and suggest future directions.